The changing clinical pattern of endemic Burkitt lymphoma in Western Africa: Experience from a tertiary center in Ghana. Issue 10 (6th June 2018) - Offor, Ugonna T.; Akyea, Ralph K.; Neequaye, Janet E.; Renner, Lorna A.; Segbefia, Catherine I.
Abstract: Background: Burkitt lymphoma (BL) is the most common childhood cancer in Ghana, where the endemic variant is the predominant subtype and historically presents as a highly chemo‐sensitive jaw tumor. This study aimed to update the current epidemiological characteristics of childhood BL in our institution. Procedure: Patient data for all children diagnosed with BL and seen at Korle Bu Teaching Hospital between January 2007 and December 2012 were retrospectively analyzed. Results: BL was diagnosed in 173 children (<13 years) during the study period, with the abdomen as the most common tumor site (46%) followed by the jaw (31%). Abdominal tumors were associated with advanced/disseminated disease ( P = 0.002), and were more likely to occur in females irrespective of tumor stage (relative risk = 1.56 [95% CI; 1.1–12.3]). Twenty‐five percent (43/173) of the study cohort died and mortality was influenced by increasing age ( P = 0.02) and advanced disease ( P = 0.03). Treatment delay was experienced by nine in ten patients primarily due to familial financial constraint (75%). Treatment abandonment was observed as a first event in 94% of patients and two thirds of children in the study were eventually lost to follow‐up. Conclusion: The predominance of primary abdominal tumors in our study cohort may indicate a changing epidemiological pattern of BL in Ghana. High rates of treatment delay and abandonment were evident and are likely to be contributing factors to the poor childhood cancer survival outcomes seen in resource‐limited countries in Africa.